Peran Modal Sosial Dalam Pengembangan Pariwisata di Desa Wisata Serangan - Ardina, Ni Ketut Rai; Kamajaya, Gede; Krisna Aditya, I Gusti Ngurah Agung (JURNAL ILMIAH SOSIOLOGI: SOROT; Vol 5 No 1 (2025): JISSOROT, 2025)
This study aims to examine the role of social capital in tourism development in Serangan Tourism Village, located in South Denpasar. Social capital is considered as one of the important assets in developing tourism, because it can increase community participation and promote sustainable tourism activities. This study will explain how social capital has a very important role in increasing and also developing tourism to Serangan Tourism Village tourism from the application and understanding of the social system that exists in society. Social capital includes Trust, Social Norms (Norms and Effective Sanctions) and Networks (Social Network). In the development of tourism in Serangan Tourism Village, social capital can be developed from a Trust that arises between the community in Serangan Tourism Village and the existence of social norms applied by the community and tourists visiting Serangan Tourism Village and also encouraged by the emergence of cooperation with parties who are able to attract tourists to visit. The conclusion that can be drawn is the role of social capital as a key factor in strengthening tourism development in Serangan Tourism Village. Keywords: Capital, Tourism, Trust, Norms, Networks.